Redistribusi Pendapatan Dan Kekayaan Telaah Surat Al Hasyr Ayat 7 - Fitri, Mulyana (AGHNIYA : Jurnal Ekonomi Islam, 2024)
The purpose of this study is to analyze how the concept of redistribution of income and wealth is based on a study of QS Al-Hasyr verse 7. This study uses library research methods using reference sources from books and journals that are appropriate to the theme. The results of this study are first, so that wealth should not be concentrated only in certain groups, but can be distributed to all levels of society. Second, so that the general public who participate in producing national welfare can obtain fair and appropriate rewards.